Lagged Effect of Parental Warmth on Child-to-Parent Violence through Moral Disengagement Strategies - Nazaret Bautista-Aranda; Lourdes Contreras; M. Carmen Cano-Lozano (MDPI AG, 2024)
Empirical evidence supports the simultaneous relationship between parental warmth and child-to-parent violence (CPV). However, no studies analyze the lagged effects of perceived parental warmth and the potential impact of cognitive mechanisms legitimizing immoral behavior on this relationship. This study aimed to examine the mediating role of moral disengagement strategies (reconstruction of immoral behavior, obscuring personal responsibility, misrepresenting injurious consequences, and blaming the victim) in the relationship between the perceived paternal and maternal warmth dimensions (warmth-communication and criticism-rejection) during childhood and CPV towards the father and mother. The sample included 2122 Spanish adolescents (57.7% female) aged 13 to 18 years. The Child-to-Parent Violence Questionnaire (CPV-Q), the Mechanisms of Moral Disengagement Scale (MMDS-S), and the Warmth Scale were used as assessment instruments. The results indicate that paternal and maternal warmth-communication is negatively associated with CPV, whereas paternal and maternal criticism-rejection and moral disengagement strategies are positively related to CPV. The mediation models show that the reconstruction of immoral behavior plays a crucial mediation role in the relationship between paternal and maternal warmth-communication and CPV as well as in the relationship between maternal criticism-rejection and CPV. The results emphasize the necessity of early prevention programs for parents promoting positive parenting practices, including parental warmth, to foster children's adaptive socio-cognitive development. In addition, addressing moral disengagement in adolescents could help prevent or stop a pattern of violent behavior toward parents.